Pangsa Pasar Penumpang Maskapai Lion Air di Bandara Pattimura Ambon - Lukiana Lukiana (Research and Development Agency of The Ministry of Transportation, 2013)
Increasing number of Airline companies in Indonesia result in increasing domestic market share competition. One of the airline in Indonesia is Lion Air which has a large fleet. One of the airport that has a growth rate of air transport demand is Pattimura airport in Ambon. The aim of this research was to determine the Strenght, Weaknesses, Opportunities and Threat (SWOT) of Lion Air in Pattimura Airport, Ambon. The goal is to provide an input to Lion Air in order to maintain and increase the air transport services in Pattimura Airport. This research used Diskriptif Quantitative analysis and SWOT method. From the calculation and rating for each of the IFAS and EFAS seen that the position of Lion Air is located in Quadrant II, namely quadrants strategy Strength - Threat at coordinates (0.67 ; 0.52). It means that Lion Air has an internal strength as a strong factor to take advantage of existing opportunities. Perusahaan penerbangan yang berjumlah 16 semakin meningkatkan persaingan dalam pangsa pasar domestik. Salah satunya adalah maskapai Lion Air dengan jumlah armada yang besar. Salah satu bandara yang mempunyai tingkat pertumbuhan permintaan angkutan udara cukup tinggi adalah bandar udara Pattimura-Ambon.Maksud kajian adalah untuk mengetahui keunggulan, kelemahan, peluang, dan tantangan yang dimiliki oleh perusahaan penerbangan Lion Air. Tujuannya adalah memberikan bahan masukan kepada Lion Air dalam upaya mempertahankan penyediaan layanan jasa angkutan udara di Bandara Pattimura-Ambon. Metodologi yang digunakan dalam penelitian ini Diskriptif Kuantitatif analisis dan SWOT. Dari hasil perhitungan pembobotan dan rating untuk masing-masing IFAS dan EFAS terlihat bahwa posisi PT. Lion Mentari Air terletak pada Kuadran II, yaitu kuadran yang menerapkan strategi Strength-Threat, pada koordinat (0,67; -0,52), di mana hal ini berarti bahwa Lion Air memiliki kekuatan sebagai faktor internal yang kuat untuk memanfaatkan peluang yang ada.